A Linguistic Study of Discursive Indications in the Ayah of Notification - Hassan Obaied Al-Ma'mori; Ameen Obaied Chichan (Periodica Journal, 2022)
The present study tackles ayah of notification in the Glorious Quran, which states; “O messenger, deliver what has been revealed to you from your Lord, And if you do it not, then you have not delivered his message, and Allah will protect you from the people. Surely Allah will not guide the unbelieving people” (Surat AlMa’eda: 67). The present study focusses on the discursive significance in this ayah as it has a unique stylistic systems, which have a great influence on the discursive significance it includes. The aim is to show the importance of the expressive intentions therein. The study discusses four methods of notification employed in this ayah, including notification through advocating, command, condition, and predicate. These styles were all employed in this ayah to confirm a great matter that the ayah was revealed in order to convey to people. The study aims at exploring the sequence of these styles and its influence on its expressive indications.
Keywords: Discourse; style; advocating; condition